Investigating Sulforaphane's anti-virulence and anti-quorum sensing properties against Pseudomonas aeruginosa - Mahmoud M. Bendary; Mohamed A. M. Ali; Mohamed A. M. Ali; Alyaa S. Abdel Halim; Fehmi Boufahja; Anis Ahmad Chaudhary; Amr Elkelish; Amr Elkelish; Rania H. M. Soliman; Wael A. H. Hegazy; Wael A. H. Hegazy (Frontiers Media S.A., 2024)
BackgroundP. aeruginosa, a significant bacterium, can cause severe illness and resistance to antibiotics. Quorum sensing (QS) systems regulate virulence factors production. Targeting QS could reduce bacteria pathogenicity and prevent antibiotic resistance. Cruciferous vegetables contain sulforaphane, known for its anti-inflammatory, antioxidant, anticancer, and antimicrobial properties.AimWe aimed to examine the inhibitory influences of sulforaphane, at a sub-inhibitory concentration (¼ minimum inhibitory concentration, MIC), on virulence and QS in P. aeruginosa.Materials and methodsThe sulforaphane's anti-virulence actions at sub-inhibitory concentrations were explored in vitro and in vivo. A sub-MIC concentration of sulforaphane was combined with anti-pseudomonal drugs, and the results of this combination were assessed. The virtual affinity of sulforaphane for the receptors of QS was studied, and its effect on the expression of QS genes was quantified.ResultsSulforaphane significantly decreased the biofilm formation, motility, ability to withstand oxidative stress, and the synthesis of virulence extracellular enzymes such as proteases, hemolysins, and elastase, as well as other virulence factors like pyocyanin. In addition, sulforaphane lessened the severity of P. aeruginosa infection in mice. Sulforaphane reduced the antipseudomonal antibiotics' MICs when used together, resulting in synergistic effects. The observed anti-virulence impacts were attributed to the ability of sulforaphane to inhibit QS via suppressing the QS genes' expression.ConclusionSulforaphane shows promise as a potent anti-virulence and anti-QS agent that can be used alongside conventional antimicrobials to manage severe infections effectively. Furthermore, this study paves the way for further investigation of sulforaphane and similar structures as pharmacophores for anti-QS candidates.